Modulating the immune system to prevent pre term labour. (18th April 2012) - Malawana, J; Mohammed, N; Howe, L; Bennett, P; Johnson, M
Abstract : Rates of preterm delivery are increasing across the developed world and range between 8-13%. Overall, preterm delivery is the most important cause of perinatal morbidity and mortality; with most problems occurring in babies born before 32 weeks. In this group, preterm labour (PTL) is most commonly caused by infection/inflammation, prompting the search for agents that can modulate the maternal inflammatory response, thereby reducing rates of PTL. We use a proven mouse model of inflammatory PTL based on the administration of lipopolysaccharide (LPS), a major cell-wall component of gram-negative bacteria, which activates the innate immune system via the toll-like receptor type 4. In this study, we used phospodiesterase (PDE) inhibitors to modulate the maternal immune system in an attempt to improve rates of pup survival and prolong pregnancy. We administered 10ug of LPS into the right horn of the uterus, at laparotomy, performed on E16 of gestation in CD1 outbred mice. 2 hours prior to this we administered our agent or DMSO vehicle diluted in PBS (control) via intraperitoneal injection. We were able to demonstrate a significant delay in labour by inhibiting the PDE4 enzyme. We were also able to demonstrate improvements in fetal outcome through the inhibition of the PDE3 enzyme. These data suggest that inhibition of PDE4 may prolong pregnancy, but that it does not appear to improve fetal outcomes. Further studies will define the mechanisms by which PDE 3 and 4 enzyme inhibition delays parturition and/or improves fetal outcomes and define whether this approach might be clinically useful.